Peran Guru Pendidikan Agama Islam (PAI) dalam Membentuk Akhlakul Karimah Perspektif teori Al Ghazali Era Media Sosial Pada Siswa Kelas IV SDN 02 Panggungrejo - Khoirotunnisa Khoirotunnisa; Salamun Salamun; Maya Aulia (UIN Fatmawati Sukarno Bengkulu, 2025)
Abstract: The noble character among students has not been formed properly, indicated by the ongoing bullying among students, lying, instant behavior and lack of discipline. The purpose of this study is to describe and analyze the role of Islamic religious education (PAI) teachers in forming noble character from the perspective of Al Ghazali’s theory in the Social Media Era in grade students IV SDN 02 Panggungrejo Lampung. Using qualitative methods with a descriptive approach. Data were collected through interviews, questionnaires, documentation, and literature reviews, and analyzed using data reduction, data display, and verification techniques. The results of the study can be concluded that the role of Islamic religious education (PAI) teachers in forming noble morals from the perspective of Al Ghazali’s theory of social media is very diverse, it is known that students really like the story method (qishah). This method shows results of 54.15% of the opinions of 24 students. So the role of preachers is very relevant, with the use of this method, because preaching is currently trending in society. So it can be suggested that teachers are expected to have spiritual intelligence, to deal with the behavior of students in the social media era. Because the social media era has positive influences, such as increasing students’ creativity and insight, and negative influences, such as decreasing interest in learning and the formation of negative behavior in students at school.Keywords: The Role of Islamic Religious Education Teachers, Akhlakul Karimah, Al Ghazali’s Theory, Social Media Era. Abstrak: Akhlak karimah dikalangan siswa belum terbentuk secara baik, ditandai masih terjadi bulliying diantara siswa, perilaku bohong, instan dan tidak disiplin. Tujuan penelitian ini untuk mendeskripsikan dan menganalisis peran guru pendidikan agama Islam (PAI) dalam membentuk akhlakul karimah perspektif teori Al Ghazali Era Media Sosial pada siswa kelas IV SDN 02 Panggungrejo Lampung. Menggunakan metode kualitatif dengan pendekatan deskriptif. Data dikumpulkan melalui wawancara, angket, dokumentasi, dan riview literature, serta dianalisis dengan tekhnik reduksi data, display data, dan verifikasi. Hasil penelitian dapat disimpulkan bahwa peran guru pendidikan agama Islam (PAI) dalam membentuk akhlak karimah perspektif teori Al Ghazali eram media sosial sangat beragam, diketahui siswa sangat menyukai metode cerita (qishah). Metode ini menunjukkan hasil sebesar 54,15% dari pendapat 24 siswa. Maka peran pendakwah sangat relevan, dengan penggunaan metode ini, karena dakwah saat ini sedang trend di kalangan masyarakat. Sehingga dapat disarankan guru diharapkan memiliki kecerdasan spiritual, untuk menghadapi tingkah laku siswa era media sosial. Karena era media sosial terdapat pengaruh posotif, seperti meningkatkan kreativitas dan wawasan siswa, dan pengaruh negative, seperti menurunnya minat belajar dan terbentuknya prilaku negatif pada siswa di sekolah.Kata kunci: Peran, Guru Pendidikan Agama Islam, Akhlakul Karimah, Teori Al Ghazali, Era Media Sosial.